The Effect of Tax Revenue Structure on Economic Growth - Kotrbová, Martina (2025)
This thesis investigates the relationship between changes in the tax revenue composition and economic growth using a balanced panel dataset of 33 developed countries from 2000–2020. We employ fixed effects and random effects regression models to test three partial research hypotheses: (1) the share of income taxes in tax revenue affects economic growth; (2) the share of property taxes in tax revenue affects economic growth; (3) the share of consumption taxes in tax revenue affects economic growth. The econometric model specification builds on the endogenous growth model proposed by Barro (1990), which is described in depth. The results suggest disparities in the impacts of tax revenue structure among higher- and lower-income countries. While shifting the tax mix toward income taxes strictly hinders economic growth in the higher-income sample, lower-income countries could benefit from relying more on corporate income taxes. Shifting the tax mix toward property and consumption taxes enhances economic growth, with the most beneficial impacts observed with a one-year lag in the lower-income countries.